6‐Shogaol induces apoptosis in acute lymphoblastic leukaemia cells by targeting p53 signalling pathway and generation of reactive oxygen species. Issue 13 (3rd May 2021) - Najafi Dorcheh, Somayeh; Rahgozar, Soheila; Talei, Daryush
Abstract: Combination therapies, using medicinal herbs, are broadly recommended to attenuate the chemotherapy adverse effects. Based on our previous findings considering the anti‐leukaemic effects of ginger extract on acute lymphoblastic leukaemia (ALL) cells, the present study was aimed to investigate the anti‐cancer role of this pharmaceutical plant on ALL mice models. Moreover, we worked towards identifying the most anti‐leukaemic derivative of ginger and the mechanism through which it may exert its cytotoxic impact. In vivo experiments were performed using five groups of six C57BL/6 nude mice, and the anti‐leukaemic activity of ginger extract alone or in combination with methotrexate (MTX) was examined. Results showed increased survival rate and reduced damages in mice brain and liver tissues. Subsequently, MTT assay demonstrated synergistic growth inhibitory effect of 6‐shogaol (6Sh) and MTX on ALL cell lines and patients primary cells. Eventually, the molecular anti‐neoplastic mechanism of 6Sh was evaluated using Bioinformatics. Flow cytometry illustrated 6Sh‐mediated apoptosis in Nalm‐6 cells confirmed by Western blotting and RT‐PCR assays. Further analyses exhibited the generation of reactive oxygen species (ROS) through 6Sh. The current study revealed the in vivo novel anti‐leukaemic role of ginger extract, promoted by MTX. Moreover, 6‐shogaol was introduced as the major player of ginger cytotoxicity through inducing p53 activity and ROS generation.